2017
DOI: 10.18203/2349-3291.ijcp20174650
|View full text |Cite
|
Sign up to set email alerts
|

Study of hepatic involvement in children with dengue infection

Abstract: Background: Liver dysfunction in children is variable and depends on disease severity. This study was undertaken to identify the range of hepatic involvement in children with dengue infection.Methods: It is a cross sectional observational study conducted in serologically positive dengue fever in children aged between 1-14 years. Hepatic function was studied in all suspected cases over a period of 1 year from June 2015 to June 2016.Results: Out of 55 cases admitted, liver function tests showed AST levels elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The manifestations of liver involvement such as nausea, vomiting, pain in the right hypochondrium, hepatomegaly, varying degrees of jaundice and an increase in liver markers principally AST and ALT. The previous studies showed liver dysfunction is more common in DSS and DHF than classical dengue fever [16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of liver involvement such as nausea, vomiting, pain in the right hypochondrium, hepatomegaly, varying degrees of jaundice and an increase in liver markers principally AST and ALT. The previous studies showed liver dysfunction is more common in DSS and DHF than classical dengue fever [16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%